Внедрение инновационных технологий в высшую школу на примере диалогового обучения - Радченко, Т.А.; Радченко, П.Н. (My University, 2016)
The article deals with the innovative technologies in higher education, as well as the concept and the essence of the dialogue learning and methods for its use.
Keywords: dialogue learning; reflection; «Education through dialogue»; «teacher-pupil»; «pupilpupil»